Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability

Adsorption of octadecyltrichlorosilane on Si(100)/SiO2 and SBA-15 - Mirji, S. A. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on Si(100)/SiO2 substrate and mesoporous SBA-15 has been studied by energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is used to study the adsorption kinetics of OTS on Si(100)/SiO2 and thermal stability of adsorbed OTS layer. Thermogravirnetric (TGA) technique is employed to understand the thermal behavior of OTS adlayer on SBA-15. Langmuir isotherms fit very well with OTS adsorption kinetics data on Si(100)/SiO2 and furnish adsorption rate constant, k(a) = 236 M-1 s(-1), desorption rateconstant, k(d) = 0.0082s(-1) and Gibbs free energy of adsorption, Delta G(ads) = -6.28 kcal mol(-1). EDAX and XPS results both show increased carbon content due to OTS adsorption and decreased oxygen and silicon content due to screening of these elements by OTS adlayer. FTIR data shows methylene (-CH2) and methyl (-CH3) stretching bands, in close agreement with reported data. The OTS layers are found to be thermally. stable up to a temperature of approximate to 260 degrees C on both Si(100)/SiO2 and SBA-15. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Gibbs free energy; OTS; SBA-15; Self-assembly; Si(100)/SiO2; thermal stability

Metal-induced reductive ring opening of 1,2,4,5-tetrazines: Three resulting coordination alternatives, including the new non-innocent 1,2-diiminohydrazido(2-) bridging ligand system - Maji, Somnath; Sarkar, B.; Patra, S.; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
{Reaction of 3,6-diaryl-1,2,4,5-tetrazines (aryl = R = phenyl, 2-furyl or 2-thienyl) with 2 equiv of Ru(acac)(2)(CH3-CN)(2) results in reductive tetrazine ring opening to yield diruthenium complexes [
Keywords: crystal engineering; hydrogen bonds; molecular; recocynition; Self-assembly; supramolecular chemistry

Polyethylene waxes: catalytic synthesis by ti-biphenolates - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Macromolecular Science Part A‐Pure and Applied Chemistry, 2007)
{Soluble complexes of Ti (IV) bearing biphenol groups such as 1,1'-binaphthelene 2, 2' diol (Binol), 1, 1'-methylene di-2-naphthol, biphenol were prepared and characterized. These catalyst precursors formulated as [
Keywords: fibers; Nanoparticles; Self-assembly

Correlation of architecture with excimer emission in 100% pyrene-labeled self-assembled polymers - Kaushlendra, K.; Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2011)
Pyrene was incorporated as pendant unit to side-chain urethane methacrylate polymers having a short ethyleneoxy or a long polyethyleneoxy spacer segment. The short-spacer pyrene urethane methacrylate was also incorporated either as block or random copolymer (1:9) along with polystyrene. The excimer emission was observed to be different for different polymers with the random copolymer exhibiting the lowest efficiency. But, the total quantum yield was highest (phi = 0.58) for random copolymer due to the high emission coefficient of monomer compared to that of excimer. The polymer dynamics were compared by steady state emission and fluorescence decay in THF or THF/water (9:1) solvent mixture and films. The solid state decay profile showed decay without a rise time indicating presence of ground state aggregates. In THF/water (9:1), the decay profile at the excimer emission (500 nm) showed a rise time indicating dynamic excimers. The evolution of excimeric emission centred similar to 430 or similar to 480 nm as a function of temperature was also studied in THF/water (9:1). The I(E)/I(M) ratio for the lambda(343) nm excitation exhibited steady increase with temperature with the block copolymer PS-b-PIHP exhibiting the highest ratio and highest rate of increase; whereas, the random copolymer PS-r-PIHP had the lowest I(E)/I(M) ratios. (C) 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 49: 1678-1690, 2011
Keywords: I(E)/I(M) ratio; Morphology; pyrene; Self-assembly; structure-property relations; time-resolved and variable temperature fluorescence

Hydrolytic conversion of a metal-organic polyhedron into a metal-organic framework - Mallick, Arijit; Garai, Bikash; Diaz, David Diaz; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: cage compounds; crystal engineering; hydrophobic effect; metal-organic frameworks; Self-assembly

Hydrophobic and hydrophilic balance and its effect on mesophase behaviour in hydroxyalkyl ethers of methyl glucopyranoside - Singh, Madan K.; Xu, Rui; Moebs, Sylvie; Kumar, Anil; Queneau, Yves; Cowling, Stephen J.; Goodby, John W. (Chemistry-A European Journal, 2013)
Four series of monosubstituted methyl -D-glucopyranoside hydroxyalkyl ethers were prepared and their thermotropic and lyotropic self-organising properties were investigated in terms of the hydrophobichydrophilic balance with respect to their molecular structures. The results obtained lead us to a new understanding of the forces that drive the formation of condensed soft-matter phases.
Keywords: carbohydrates; liquid crystals; mesophases; Self-assembly; soft matter

Influence of the sophorolipid molecular geometry on their self-assembled structures - Dhasaiyan, Prabhu; Banerjee, Agnimitra; Visaveliya, Nikunjkumar; Bhagavatula L. V. Prasad (Chemistry-an Asian Journal, 2013)
Keywords: bolaamphiphiles; helical structures; p-p stacking; Self-assembly; sophorolipids

Large centimeter-sized macroporous ferritin gels as versatile nanoreactors - Kumari, Sushma; Kulkarni, Amol; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemistry of Materials, 2013)
Organized assemblies of bionanoparticles such as ferritin provides templates that can be exploited for nanotechnological applications. Organization of ferritin into well-defined three-dimensional assemblies is challenging and has attracted considerable attention recently. We have synthesized, for the first time, large (centimeter-sized) self-standing macroporous scaffold monoliths from ferritin bionanoparticles, using dynamic templating of surfactant H-1 domains. These scaffolds comprise three-dimensionally connected strands of ferritin, organized as a porous gel with porosity similar to 55 mu m. The iron oxide inside the ferritin scaffold can be easily replaced with catalytically active monodisperse zerovalent transition metal nanoparticles using a very simple protocol. Since the ferritin is cross-linked in the scaffold, it is significantly robust with enhanced thermal stability and better tolerance toward several organic solvents in Comparison to the native ferritin bionanoparticle. In addition, the scaffold macropores facilitate substrate and reagent transport and hence the monoliths containing active Pd or iron oxide nanoparticles inside apo-ferritin bionanoparticles were used as a recyclable heterogeneous catalyst for the oxidation of 2,3,6-trimethyl phenol to 2,3,6-trimethyl-1,4-benzoquinone (precursor for Vitamin E synthesis) and for Suzuki-Miyaura cross-coupling reaction in both aqueous and organic solvents. The protein shell around the nanoparticles protects them from agglomeration, a phenomenon that otherwise plagues nanoparticles-based catalysis. The presence of macropores allow the ferritin scaffold to act as catalytic monolith for continuous flow reactions having rapid reaction rates, while offering a low pressure drop. Finally, the Pd@apo-ferritin scaffold was immobilized inside a steel cartridge and used for the continuous flow hydrogenation of alkenes to their corresponding alkanes for 15 cycles without any loss of activity.
Keywords: catalysis; continuous flow; ferritin; gel; macroporous materials; Self-assembly

Dilution does the trick: role of mixed solvent evaporation in controlling nanoparticle self-assembly - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
An easy and convenient way to prepare superlattices of amine capped gold nanoparticles is presented. It is clearly established that solvent evaporation significantly influences the nature of resulting superlattices and critically governs whether monolayer or multilayer superlattices are formed. More specifically, it is demonstrated that dilution of the nanoparticle dispersion with a similar solvent (but with different vapour pressure) is an expedient handle to control the nature of self-assembly. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Evaporation rate; gold nanoparticles; Nucleation; Self-assembly

Effect of self-assembly on triiodide diffusion in water based polymer gel electrolytes: an application in dye solar cell - Soni, S. S.; Fadadu, K. B.; Vekariya, R. L.; Debgupta, Joyashish; Patel, K. D.; Gibaud, A.; Aswal, Vinod K. (Journal of Colloid and Interface Science, 2014)
The preparation of ordered polymer gels from the amphiphilic block copolymers, Pluronic (R) F77, P123 and polyethylene glycol in the presence of ionic liquid, iodine and organic additives is presented. At 35%(w/w) concentration these copolymers (F77 and P123) self-assembled into cubic liquid crystalline phase in aqueous solution and characterized by using SAXS and AFM measurements. The effects of micellar aggregation formed by polymers on the ionic transport and triiodide diffusion have been studied by electro-chemistry and SANS experiments. The ionic migration or triiodide diffusion through these polymer gels is found to be affected by the PEO/PPO content in the polymer backbone. These gels were successfully employed as an electrolyte in a dye sensitized solar cell. A remarkable solar to electricity conversion efficiency and good stability was obtained using Pluronic (R) F77 based gel, which is attributed to its thermoreversible sol to gel transition. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Amphiphilic block copolymer; Dye solar cell; Micellar nanochannels; SANS; SAXS; Self-assembly; Water based gel electrolytes

Functional silicon nanostructures derived from drying-mediated self-assembly of gold nanoparticles - Deshmukh, Ashvini B.; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Journal of Nanoparticle Research, 2014)
Self-assembly of nanoparticles is an efficient technique where nanobuilding blocks spontaneously organize into ordered structures by thermodynamic and other constraints. We demonstrate that multifunctional Silicon (Si) nanostructures with unique morphologies like sheets, plates and flakes can be etched chemically by taking an advantage of natural self-assembly of gold nanoparticles (AuNPs) characterized with drying kinetics under external stimuli. We further demonstrated antireflection properties of the as-synthesized Si nanostructures.
Keywords: Antireflective material; gold nanoparticles; Metal-assisted chemical etching; Self-assembly; Si Nanostructures

Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

Vesicle structures from bolaamphiphilic biosurfactants: experimental and molecular dynamics simulation studies on the effect of unsaturation on sophorolipid self-assemblies - Dhasaiyan, Prabhu; Pandey, Prithvi Raj; Visaveliya, Nikunjkumar; Roy, Sudip; Bhagavatula L. V. Prasad (Chemistry-A European Journal, 2014)
The formation of giant-vesicle-like structures by self-assembling linolenic acid sophorolipid (LNSL) molecules is revealed. Sophorolipids belong to the class of bolaamphiphilic glycolipid biosurfactants. Interestingly, the number of double bonds present in the hydrophobic core of sophorolipids is seen to have a great influence on the type of self-assembled structures formed. Dye encapsulation results establish the presence of an aqueous compartment inside the LNSL vesicles. Molecular dynamics simulation (MD) studies suggest the existence of two possible conformations of LNSLs inside the self-assembled structures and that LNSL molecules arrange in layered structures.
Keywords: bolaamphiphiles; MD simulations; Self-assembly; sophorolipids; vesicles

P4VP and oligo(phenylenevinylene)-perylenebisimide mixed donor-acceptor supramolecular comb polymer complexes with improved charge carrier mobility - Saibal, B.; Chithiravel, Sundaresan; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Random donor-acceptor (D-A) supramolecular comb polymers were formed when hydroxyl functionalized donor and acceptor small molecules based on Oligo(phenylenevinylene) (named OPVCN-OH) and Perylenebisimide (named UPBI-PDP), respectively, were complexed with Poly(4-vinyl pyridine) (P4VP). A series of random D-A supramolecular comb polymers were formed by varying the ratios of UPBI-PDP and OPVCN-OH with P4VP. A 100% P4VP-donor polymer complex [P4VP(OPV1.00)] and a 100% P4VP-acceptor polymer complex [P4VP(UPBI1.00)] were also synthesized and characterized. Complex formation was confirmed by FT-IR and H-1 NMR spectroscopy. Solid state structural studies carried out using small angle X-ray scattering and wide angle X-ray diffraction experiments revealed altered packing of the D and A molecules in the complexes. Transmission electron microscopy images showed lamellar structures in the <10 nm scale for the P4VP(OPV1.00), P4VP(UPBI1.00), and mixed P4VP (D-A) complexes. The effect of the nanoscopic D-A self-assembly on the bulk mobility of the materials was probed using SCLC measurements. The mixed D-A random complexes exhibited ambipolar charge transport characteristics with higher values for the average bulk hole mobility estimate. P4VP(OPV0.25+UPBI0.75) exhibited an average hole mobility in the order of 10(-2) cm(2) V-1 s(-1) and electron mobility 10(-5) cm(2) V-1 s(-1). (C) 2016 Wiley Periodicals, Inc.
Keywords: donor-acceptor; oligo(phenylenevinylene); P4VP; Perylenebisimide; Self-assembly; structure-property relations; supramolecular comb polymer; supramolecular structures

Liquid crystalline supramolecular crosslinked polymer complexes of ditopic rylenebisimides and P4VP - Saibal, B.; Narayan, Rekha; Chithiravel, S.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Perylenebisimide and naphthalenebisimide (PBIPDP and NBI-PDP) end functionalized with pentadecyl phenol is designed as ditopic hydrogen bonding acceptors to form supramolecular crosslinked network with poly(4-vinyl pyridine) (P4VP). The pristine PBI-PDP has been grown as single crystals from DCM-MeOH (dichloromethane-methanol) mixture at room temperature, which revealed a P21 space group. Noticeably, the pentadecyl alkyl chain shields the aromatic perylene core on both sides resulting in the absence of p-p interaction in single-crystal assembly. The naphthalenebisimide derivative exhibits thermotropic liquid crystalline behavior, while both the molecules exhibits lyotropic liquid crystalline phases in tetrahydrofuran (THF), which were characterized using a combination of differential scanning calorimeter, X-ray diffraction, and polarized light microscopy. The hydrogen-bonded complex of both the rylenebisimides with P4VP preserves the mesomorphic properties in THF. The electron transport mobility measured by space charge limited current measurements reveals a two orders of magnitude increase in the charge transport in the P4VP complex compared to that of the pristine molecule. The average electron mobility obtained is mu(e, avg): 10(-3) cm(2)/Vs for P4VP-PBI compared to mu(e, avg): 10(-5) cm(2)/Vs for pristine PBI derivative. (C) 2017 Wiley Periodicals, Inc.
Keywords: crystal structures; ditopic rylenebisimide; hydrogen bonding; lyotropic liquid crystal; P4VP; Self-assembly; supramolecular crosslink; supramolecular structures

Interaction of polymers with amyloidogenic peptides - Abraham, Jancy Nixon; Nardin, Corinne (Polymer International, 2018)
With this review, the aim was to gather recent representative publications which describe the interaction of polymers with amyloidogenic peptides/proteins. When functional, these take part in for instance bacterial adhesion and biofilm formation. However, several of the peptides/proteins have been identified in various diseases. One of the current approaches to discover a cure against these relies on therapeutics which either prevent or accelerate peptide/protein aggregation and/or clear readily formed aggregates. Owing to the common interest of scientists from all disciplines to identify a cure against the diseases of public health concern, there are overwhelming numbers of publications dealing with these two approaches. Since amyloid aggregation could be regarded as a nucleated polymerization, which is an established mechanism of polymer self-assembly, we recently tackled the issue of amyloid aggregation using the theories and methods established in polymer science. In this review, we hence focus on gathering relevant and recent publications which describe the role of polymers in modulating the aggregation of amyloidogenic peptides/proteins. (c) 2017 Society of Chemical Industry
Keywords: amyloid; neurodegenerative diseases; Polymer; protein; Self-assembly

Novel pentadecyl phenol-tagged L-tryptophan molecules: synthesis, self- assembly and liquid crystalline properties - Parappurath, Akhil; Abraham, Jancy Nixon (Chemistryselect, 2018)
The paper describes the self-assembly and liquid crystalline properties of pentadecylphenol tagged L-tryptophan molecules having ester and amide functionality. We have synthesized a series of molecules having mono and ditryptophan moieties attached to pentadecylphenol through amide or ester linkage. The fluorescence properties of the Boc-L-tryptophan-pentadecylphenol molecules were measured in methanol and found to aggregate beyond the critical aggregation concentration and self-assembled to give spherical structures. Upon deprotection of Boc group, the amine end group got involved in extended hydrogen bonding and fibril like structures were developed. These molecules also showed liquid crystalline behavior in hydrogen bonding solvents such as benzyl alcohol and showed needle like crystals in tert-butanol, as analyzed by polarized optical light microscopy.
Keywords: Cardanol; liquid crystalline; pentadecylphenol; Self-assembly; Tryptophan

Phase diagram of self-assembled sophorolipid morphologies from mesoscale simulations - Sarkar, Sujit; Chakraborty, Souvik; Roy, Sudip (Journal of Molecular Liquids, 2018)
We have constructed a phase diagram from the self-assembled morphologies of linolenic acid sophorolipid in water by performing mesoscale simulations in different concentrations. The dependence of morphologies and its properties of the self-assembled structure as a function of the concentration of bolaamphiphile in water are investigated. Two hydrophilic head groups and one hydrophobic tail group of bolaamphiphile have been mapped to beads for mesoscale simulation. The interaction parameters between different beads are calculated using Flory-Huggins solution theory. Flory-Huggins x-parameters have been calculated from atomistic simulation and experimental data of pure components constituting linolenic acid sophorolipid. We have obtained different self-assembled morphologies depending upon the concentrations of sophorolipid in water. We have explored the arrangements of hydrophobic and hydrophilic groups of the sophorolipid chains in the different morphologies. The sophorolipid chains found to be present in different structural arrangements. The residence time and flip frequency of these lipids in different orientations have been calculated and discussed in this work. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Bolaamphiphile; Flip frequency; Mesoscale simulation; Orientation of chains; Self-assembly

Supramolecular complexes of poly(3‐Hexylthiophene)‐block (and random)‐poly[3‐(2‐(6‐carboxyhexyl)methyl)thiophene] copolymers with perylene bisimide - Shinde, Shekhar (Journal of Polymer Science Part A: Polymer Chemistry, 2018)
Block and random copolymers of poly(3‐hexylthiophene) and poly[3‐(2‐(6‐carboxyhexyl)methyl)thiophene] with side‐chain carboxylic functionality ((P3HT‐b‐P3COOH) and (P3HT‐r‐P3COOH) were developed by Grignard Metathesis (GRIM) polymerization. The carboxylic functionality was introduced in the side chain via the oxazoline route. Both the block and random polythiophene copolymers were complexed with pyridine functionalized perylene bisimide to obtain supramolecular block and random polymer complexes. The complex formation in both systems was confirmed by 1H NMR, WXRD and SAXS studies. An expansion of d spacing upon complex formation was observed in both the block and random copolymer, which could be traced by WXRD. Hole and electron mobilities measured for the supramolecular complexes indicated values which were higher by an order of magnitude for the supramolecular block complex (μh ≈ 2.9 × 10−4 cm2/Vs; μe ≈ 3.1 × 10−6 cm2/Vs) as compared to the random (μh ≈ 1.4 × 10−5 cm2/Vs; μe ≈ 4.7 × 10−7 cm2/Vs) copolymer. These results are indicative of the higher degree of disorder prevailing in the films of random copolymer system compared to the block copolymer.
Keywords: block and random polythiophene; perylene bisi-mide; Self-assembly

Self-assembly of Di-guanine peptide nucleic acid amphiphiles into fractal patterns - Abraham, Jancy N.; Pawar, Prabhakar; Kootteri, Dilna K. (ChemistrySelect, 2019)
Peptide nucleic acids (PNAs) amphiphiles have been reported to assemble into different nanostructures; however, there is immense untapped potential to control their supramolecular assemblies by altering their lipid chain. Here, we functionalized di-guanine PNA with various hydrophobic appendages, namely dodecyl, p-dodecylbenzoyl and pentadecyl phenol groups, to investigate the effect of aromatic linkers, long alkyl and alkoxyl substituents on hierarchical self-assembly of di-guanine PNA. Systematic electron microscopy and atomic force microscopy studies revealed that while all three derivatives of di-guanine-PNA formed nanospheres, only nanospheres of dodecylamide and pentadecyl phenol derivatives matured into nanorods, these later formed higher order fractal assemblies. Furthermore, we observed that inclusion of a positively charged lysine at the C-terminus prevented fractal assembly, possibly due to electrostatic repulsion between the head groups. Thus, the findings of the present work might guide rational design of PNA amphiphiles to obtain specific self-assembled morphology.
Keywords: Fractal pattern; Guanine; pentadecylphenol; Peptide nucleic acid; Self-assembly

Self-assembly of bispentadecylphenol substituted perylenediimide with PS-b-P4VP for structure-property insight into the core of core-shell micelles - Roy, Moumita; Rajamohanan, Pattuparambil R.; Ravindranathan, Sapna; Asha, S. K. (ACS Applied Polymer Materials, 2020)
We report the use of a ditopic molecular probe bispentadecylphenol substituted perylenediimide (PBI-PDP) to examine the molecular level self-assembly of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) in tetrahydrofuran (THF). A series of complexes were prepared between PS-b-P4VP copolymers with varying lengths of the 4-vinylpyridine chain and PBI-PDP. Light scattering and NMR spectroscopic studies reveal that the self-assembled structures of the solid complexes are not fully disrupted when the complexes are dissolved in THF. NMR experimental parameters measured for the small probe molecule provide detailed insights into the structure of the assemblies in solution as well as the interaction between the small molecule and the block copolymer. Such insights can have important implications in manipulating the nanostructure of block copolymer micelles to suit various application requirements. The dynamics and distribution of the PBI-PDP molecules within the assemblies in solution show a dependence on the length of the P4VP block. Transmission electron microscopy was employed to study the evolution of morphologies in films prepared from the self-assembled structures in THF solutions.
Keywords: core corona interface; ditopic molecular probe; environment; micelles; perylenediimide; PS-b-P4VP; Self-assembly

Synthesis of phospho-polypeptides via phosphate-containing N-carboxyanhydride: application in enzyme-induced self-assembly, and calcium carbonate mineralization - Mondal, Basudeb; Das, Soumen; Panda, Sidharth; Dutta, Tahiti; Sen Gupta, Sayam (ChemPlusChem, 2020)
An easy synthetic strategy was developed to synthesize the phosphate-functionalized amino acid N-carboxyanhydride (NCA), using simple primary amine initiators to obtain homo and block phospho-polypeptides with controlled molecular weight and molecular weight distribution. The methodology was extended to the synthesis of the end-functionalized homo polypeptides (15 to 50 repeat unit) and block co-polypeptides with PEG (0.7 K, 2 K, and 5 K) and glycopolypeptide (15-unit mannose glycopolypeptide) as one of the blocks. The deprotected fully water-soluble anionic phosphate-based polypeptides showed pH-dependent helical conformation with a helical content of 20 %, which further changed to beta-sheets upon addition of the enzyme alkaline phosphatase (ALP) due to dephosphorylation. The block co-polypeptide containing PEG as one of the blocks led to its self-assembly into colloidal structures, such as vesicles with a hydrodynamic diameter of similar to 250 nm, due to the formation of amphiphilic block co-polymer upon dephosphorylation. The nature of the colloidal structures formed can be temporally controlled by the extent of dephosphorylation. Finally, the phospho-polypeptides serve as a template for the mineralization of calcium carbonate with varying polymorphs and morphologies.
Keywords: Biomineralization; enzymes; phosphopolypeptides; Proteins; Self-assembly

Durable metalloporphyrin 2D-polymer for photocatalytic hydrogen and oxygen evolution from river and sea waters - Ranjeesh, Kayaramkodath Chandran; George, Leena; Maibam, Ashakiran; Krishnamurty, Sailaja; Babu, Sukumaran Santhosh (ChemCatChem, 2021)
It is highly imaginary that the outcome of a combination of two complementary resources leads to answer an alarming global issue. One such possible example is the solar seawater splitting for `clean fuel' H-2 generation. Since the catalytic activity and stability of the photocatalysts are substantially challenged in seawater, the design of an efficient and stable photocatalyst is highly desirable. Herein, we demonstrate the solar seawater splitting by a two-dimensional polymer catalyst derived from metalloporphyrin bearing multi-hydroxyl groups. A bimetallic (Co and Ni) porphyrin 2D-polymer exhibits excellent long-term durability of 15 cycles of H-2 and O-2 generation in 200 days from pure water without a considerable decrease in efficiency. Detailed studies using river and seawaters also show the reliable performance of the catalyst over repeated cycles. Here the deactivation modes of catalytic activity have been nullified by the layered metalloporphyrin polymer structure through stable pi-pi stacking, signifying the molecular design of 2D-polymer photocatalyst.
Keywords: 2D-polymer; Photocatalyst; porphyrin; Self-assembly; water splitting

i-Indigo-based self-assembled microparticles and their conversion to nanoparticles - Singh, Anup Kumar; Swain, Gitanjali (ChemistrySelect, 2023)
Microscopic particles (MPs) are used to scatter and reflect UV light. It is well established that inorganic MPs such as TiO2 and ZnO produce carcinogens. Therefore, organic MPs are explored for UV absorption. Conjugated chromophores with differing lipophilicity usually self-assemble into nanoscopic structures. In our previous experiments, unsymmetrical i-Indigo was found to self-assemble into 500 nm particles. We hypothesized that the size of the self-assembled particles can be increased by increasing the lipophilicity difference between the side chains. Toward this objective, we have chosen the i-Indigo core with TEG and alkyl chains as side chains. As a result, the i-Indigo molecules were found to self-assemble into 3 & mu; spheres in solution. By substituting side chains with different lipophilicity, i-Indigo microparticles with the size of 5 & mu; are prepared. A careful analysis showed that the spheres are similar to a soccer ball, and they deflate upon drying on the substrate surface. The judiciously chosen side chain binds with a metal-ion (Cs+) and forms nanoscopic assemblies. After Cs+ binding, the size of the particles is decreased drastically to 100 nm. The simple addition of ions converts microscopic assemblies into nanoscopic assemblies.
Keywords: Isoindigo; microparticles; Nanoparticles; Self-assembly; UV absorber

Self-assembled amino acid microstructures as biocompatible physically unclonable functions (BPUFs) for authentication of therapeutically relevant hydrogels - Akavaram, Vishwas; Kumar, Kush; Sriram, Shreya; Narra, Saisrinath; Kumawat, Akshant; Meena, Santosh Kumar; Pushpavanam, Karthik (Macromolecular Bioscience, 2023)
Counterfeited biomedical products result in significant economic losses and pose a public health hazard for over a million people yearly. Hydrogels, a class of biomedical products, are being investigated as alternatives to conventional biomedical products and are equally susceptible to counterfeiting. Here, a biocompatible, physically unclonable function (BPUF) to verify the authenticity of therapeutically relevant hydrogels are developed. The principle of BPUF relies on the self-assembly of tyrosine into fibril-like structures which are incorporated into therapeutically relevant hydrogels resulting in their random dispersion. This unclonable arrangement leads to distinctive optical micrographs captured using an optical microscope. These optical micrographs are transformed into a unique security code through cryptographic techniques which are then used to authenticate the hydrogel. The temporal stability of the BPUFs are demonstrated and additionally, exploit the dissolution propensity of the structures upon exposure to an adulterant to identify the tampering of the hydrogel. Finally, a platform to demonstrate the translational potential of this technology in validating and detecting tampering of therapeutically relevant hydrogels is developed. The potential of BPUFs to combat hydrogel counterfeiting is exemplified by its simplicity in production, ease of use, biocompatibility, and cost-effectiveness.
Keywords: anti-counterfeiting; hydrogels; physically unclonable functions; Self-assembly; translational

Surface-induced demixing of self-assembled isomeric mixtures of citral - Saraf, Deepashri; Prakash, Shikha; Pinjari, Aadil; Pujari, Bhalchandra; Sengupta, Durba (Journal of Molecular Liquids, 2023)
The self-assembly of organic molecules and their interactions with metal surfaces have been of considerable interest, both for developing novel functional materials and for understanding fundamental design principles of nanostructures. In this study, we investigate the solution and surface-induced self-assembly of two stereoisomers of citral molecules (geranial and neral) using atomistic molecular dynamics simulations. We demonstrate that the morphology of the aggregates in water is concentration dependent (ranging from distorted spherical to slab-like aggregates) but independent of isomer effects. The isomeric mixtures of citral indicate homogeneous mixing based on differential density maps and high values of Shannon entropy. Interestingly, surface-confinement of citral aggregates on a Cu(111) surface leads to phase segregation and demixing of the two isomers that is more apparent in the surface-bound monolayer in comparison to the adjacent layers. Positional ordering and formation of domains are observed over a series of isomeric citral mixtures with varying compositions, as indicated by high differential density and low values of Shannon entropy. Our work provides new insights into molecular self-assembly of organic molecules in nanostructures and metal-organic overlayers.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Citral; Isomers; Metal-organic interactions; molecular dynamics; Self-assembly; Shannon entropy

Oligo(phenyleneethynylene)s: shape-tunable building blocks for supramolecular self-assembly - Fernandez, Zulema; Sanchez, Luis; Santhosh Babu, Sukumaran; Fernandez, Gustavo (Angewandte Chemie-International Edition, 2024)
Oligo(phenyleneethynylene)s (OPEs) have attracted widespread attention due to their remarkable (opto)electronic and photophysical properties, which have enabled numerous applications. The versatile functionalization possibilities of OPEs make them unique candidates to form various shape-persistent geometries, including linear, triangular, rectangular, hexagonal and macrocyclic. However, as a result of this structural variety, it is oftentimes challenging to correlate molecular design with self-assembly properties. In this minireview, we have classified OPEs based on their molecular shapes and correlated them with their self-assembly behavior in solution. Particularly, we provide important insights into the aggregation propensity of the different molecular shapes and how to tune the association strength using various non-covalent interactions. Our classification will enable a better understanding of the structure-property correlation in OPEs, which is key to develop supramolecular functional materials.
Keywords: non-covalent interactions; Oligo(phenyleneethynylene)s; pi-conjugated systems; Self-assembly; Supramolecular Polymerizaton

Pyridazine-Based Aggregation Induced Emission Active Conjugates: Synthesis, Single Crystal XRD Analysis, and Self-Assembly Assessment - Waghchoure, Aishwarya P.; Sangale, Vijay B.; Shaligram, Parth S.; Lambud, Sushil; Pardeshi, Satish K.; Gonnade, Rajesh G.; Bandaru, Sateesh; More, Sandeep; Reddy, J. Prakasha; Bhosale, Rajesh S. (CHEMISTRYSELECT, 2024)
Keywords: AIE; Pyridazine; Self-assembly; Single crystal

Thermally stable P-chiral supramolecular phosphines, their self-assembly and implication in Rh-catalyzed asymmetric hydrogenation - Chandanshive, Amol C.; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry-A European Journal, 2024)
P-chiral supramolecular phosphine ligands are crucial for asymmetric transformations, but their synthesis is tedious. We report a one-step synthesis of thermally stable P-chiral supramolecular phosphines and their performance in the asymmetric hydrogenation of functionalized alkenes. A rational designing and synthesis of (R, R)-QuinoxP* ligated palladium complex (Pd-2) in excellent yield is reported. This Pd-2 catalyzed a direct P-C coupling of 2,3-dihydro-1-H-phosphindole (A1)/1,2,3,4-tetrahydrophosphindoline (A2) with 1-(3-iodophenyl)urea (B1)/2-iodo /6-hydroxy pyridine (B2) and,produced corresponding ligands L1-L3. The P-C coupling between A1 and B2 produced 6-(2,3-dihydro-1H-phosphindol-1-yl)pyridine-2(1H)-one (L2) with an excellent enantiomeric excess of up to 99 %. L2 was found to be remarkably stable even at 150 degrees C and did not oxidize/hydrolyze for at least 24 hours in open air. Such thermal stability and an impediment to oxidation are unprecedented. L2 self-assembled and produced L2-C1 (Pt), L2-C2(Pd), and L2-C3(Rh) assemblies. The utility of the self-assembled P-chiral ligand was demonstrated in the Rh-catalyzed asymmetric hydrogenation (AH) of functionalized olefins. The L2-C3 catalyzed AH of functionalized alkenes and delivered chiral products with excellent enantioselectivity of >99 %. A small library of 16 substrates was subjected to AH using L2-C3 to produce chiral compounds with excellent conversion and ee.
Keywords: asymmetric hydrogenation; Asymmetric phosphination; P-chiral phosphine; Self-assembly; Supramolecular phosphine

Supramolecular self-assembly of glochidonol: a renewable triterpenoid from glochidion tomentosum - Patil, Harshal S.; Jagadeesh, K. S.; Dinore, Jaysingh; Sharanappa, P.; Baviskar, Ashwini S.; Thulasiram, Hirekodathakallu V. (Chemistryselect, 2025)
Glochidonol a lupane pentacyclic (6-6-6-6-5) triterpenoid isolated from Glochidion tomentosum, exhibited exceptional gelation ability compared to the screened lupane- and oleanane-type triterpenoids. This study represents the first report on the self-assembly behavior of glochidonol in various liquids. The molecule self-assembled to form gels in all tested aromatic solvents, whereas no gelation was observed in water or phosphate buffer. The structural and physical properties of the self-assembled glochidonol were characterized using optical microscopy, scanning electron microscopy, atomic force microscopy, and Fourier-transform infrared spectroscopy. Additionally, the glochidonol-based self-assembled fibrillar network was utilized for the encapsulation of fluorescein isothiocyanate as a model drug, highlighting its potential for biomedical applications. A glochidonol-based gel loaded with doxorubicin exhibited sustained, diffusion-mediated drug release into PBS, accompanied by partial gel degradation. Fluorescence analysis confirmed release suggesting drug-gel interactions and diffusion. The glochidonol-based gel demonstrated sustained, diffusion-controlled doxorubicin release with partial degradation under physiological conditions.
Keywords: Glochidion tomentosum; Glochidonol; Organo gelator; Self-assembly; Triterpenoids

Triple G-C-T base-coded nucleobase self-assembling monomers featuring polymerizable groups for 3D printing - Gawande, Akshay J.; Kamble, Ganesh N.; Singh, Dharmendra; Sanjayan, Gangadhar. J.; Nair, Kiran Sukumaran (ACS Applied Polymer Materials, 2025)
Self-assembling monomers (SAMs) offer a versatile strategy for enhancing the performance of photoresins in Digital Light Processing (DLP) 3D printing. In this work, we report the design and synthesis of two photoprintable, nucleobase-inspired SAMs featuring a triple G-C-T base-coded hydrogen-bonding motif. This SAM was formulated using 2-hydroxyethyl acrylate (2-HEA), 1,6-hexanediol diacrylate (HDDA), and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO) to prepare UV-curable resins suitable for high-resolution DLP printing. Remarkably, the printed samples exhibited supramolecular self-assembly, facilitated by dynamic hydrogen bonding, demonstrating a notable enhancement in thermal and mechanical performance when compared to the control sample. Thermal properties evaluated by a differential scanning calorimeter revealed an increase in the glass transition temperature (T-g) from 15 degrees C to 54 degrees C for SAM-incorporated printed materials. Mechanical testing demonstrated a >200% increase in toughness and >150% improvement in tensile strength relative to the unmodified resin while maintaining or exceeding the original elongation at break (up to similar to 74%). Variable-temperature FTIR spectroscopy confirmed the presence of thermally responsive supramolecular interactions. Notably, self-healing behavior was observed in both GCT-A 15 wt % and GCT-S 15 wt % formulations, indicating partial recovery of mechanical integrity under mild thermal conditions due to reversible hydrogen bonding. These findings demonstrate the potential of SAMs as functional additives for developing robust, thermally stable, and self-healing DLP-printed materials for advanced engineering applications.
Keywords: 3D printing; hydrogen bonding; Self-assembly; Self-healing; Triple G-C-T nucleobase

Structural and mechanistic heterogeneity of the phase separation and aggregation of full-length TDP-43 is governed by environmental conditions - Doke, Abhilasha A.; Kirmire, Mona S.; Jha, Anjali; Jha, Santosh Kumar (ACS Chemical Neuroscience, 2026)
TAR DNA-binding protein 43 (TDP-43) is an essential physiological protein implicated in several fatal neurodegenerative disorders. Interestingly, the nature of TDP-43 aggregates varies across patients and disease conditions, suggesting an underlying heterogeneity in its self-assembly behavior. In this study, we investigated two native-like states of full-length TDP-43: the native dimer (N form) and the native-like oligomer (O form). These are compact, folded states with similar secondary structures but differ in size. We found that the N and O forms respond differently to external perturbations and form distinct self-assemblies under stress conditions. Under electrostatic stress, both N and O forms undergo phase separation but produce condensates with markedly different morphologies and dynamics. The underlying mechanisms driving their phase separation are different. Under thermal stress, both forms convert into amyloid aggregates, but again with clearly different morphologies, biochemical properties, and aggregation pathways. These results demonstrate that multiple conformations of TDP-43 respond to distinct perturbations by assembling into structurally and mechanistically different higher-order assemblies. Our findings highlight how the interplay among the structural state, solvation environment, and self-assembly mechanism governs the heterogeneity of TDP-43 assemblies, offering new insights into their physiological roles and pathological relevance. This study suggests that the heterogeneity observed in patients associated with TDP-43 aggregation may arise from differences in the cellular stresses experienced by the protein and the corresponding assembly mechanisms engaged.
Keywords: Amyloid-like aggregation; molecular mechanism of phase separation; native-like phase separation; Self-assembly